Bilingual atlas of livestock in the Lake Chad basin - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Atlas d elevage du Bassin du Lac Tchad Livestock atlas of the Lake Chad Basin